Carcass treatments for improved meat quality (In Swedish with Summary in English) - Wiklund, Eva (Rangifer, 2005)
Meat quality is a term that includes many different aspects like e.g. safety, ethics, nutrition, taste and functionality. What is regarded as most important is mainly related to where a person is placed in the chain from production to consumption. Along this chain are also many factors that influence the quality of meat. By measuring the pH value of meat it is possible to get good information about shelf life, tenderness, colour and water-holding capacity. Meat pH also gives an indication to whether the animals have been exposed to stress prior to slaughter or not. Good pastures and supplementary feeding using grain-based feed mixtures have been demonstrated to increase the energy stores in the animals' muscles and therefore have a positive effect on pH values in venison. What the animals had been eating prior to slaughter also affected the fat composition and meat flavour. Meat from animals grazing pasture had more polyunsaturated fatty acids and a "wild" flavour compared with meat from animals fed grain-based pellets. It is possible to change the fat composition in a commercial grain-based feed mixture, without altering the protein or energy content, so that the fat composition mimic that of a natural pasture. Pelvic suspension of a carcass will stretch the muscles in valuable cuts and improve the tenderness of the meat. In fallow deer carcasses the tenderness was improved in several meat cuts and in addition the water-holding capacity of the meat increased after pelvic suspension. Electrical stimulation of the carcass quickly empties the energy stores in the muscles and accelerates the onset of rigor mortis. In red deer venison electrical stimulation accelerated the rate of meat tenderisation, but this benefit was lost after approx. 3 weeks of ageing (-1.5 °C). A study from Alaska demonstrated no effects of electrical stimulation of reindeer carcasses on meat tenderness or water-holding capacity. We recommend further studies of pelvic suspension and electrical stimulation to get a better understanding of their effects on venison quality and to be able to implement these techniques in the most optimal way.